2016
DOI: 10.1021/acs.jafc.5b05735
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Investigation of Rhizoctonia solani AG 4 Identifies Secretome and Mycelial Proteins with Roles in Plant Cell Wall Degradation and Virulence

Abstract: Rhizoctonia solani AG 4 is a soilborne necrotrophic fungal plant pathogen that causes economically important diseases on agronomic crops worldwide. This study used a proteomics approach to characterize both intracellular proteins and the secretome of R. solani AG 4 isolate Rs23A under several growth conditions, the secretome being highly important in pathogenesis. From over 500 total secretome and soluble intracellular protein spots from 2-D gels, 457 protein spots were analyzed and 318 proteins positively mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…Many researches have reported that CWDEs are involved in the direct degradation of plant tissue, and they have been suggested to be pathogenicity factors of several pathogens, such as pectate lyase (PL), polygalacturonase (PG), etc. (Zhang et al, 2014 ; Lakshman et al, 2016 ). In this study, alkaline environment significantly inhibited the accumulation of CWDEs (Table 2 ), including 1, 3-beta-glucanosyltransferase (SP18), SPR1-exo-1, 3-beta-glucanase (SP19), glucan 1, 3-beta-glucosidase (SP20), endo alpha-1, 4 polygalactosaminidase precusor (SP21), gluconolactonase (SP23), and probable cellulose (SP24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many researches have reported that CWDEs are involved in the direct degradation of plant tissue, and they have been suggested to be pathogenicity factors of several pathogens, such as pectate lyase (PL), polygalacturonase (PG), etc. (Zhang et al, 2014 ; Lakshman et al, 2016 ). In this study, alkaline environment significantly inhibited the accumulation of CWDEs (Table 2 ), including 1, 3-beta-glucanosyltransferase (SP18), SPR1-exo-1, 3-beta-glucanase (SP19), glucan 1, 3-beta-glucosidase (SP20), endo alpha-1, 4 polygalactosaminidase precusor (SP21), gluconolactonase (SP23), and probable cellulose (SP24).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that extracellular proteins related to CWDEs or proteolysis are important for the pathogenicity of plant pathogens. The plant cell wall is an internal physical defensive barrier, and pathogens use extracellular enzymes to degrade the cell wall and invade host (Lakshman et al, 2016 ). Many researches have reported that CWDEs are involved in the direct degradation of plant tissue, and they have been suggested to be pathogenicity factors of several pathogens, such as pectate lyase (PL), polygalacturonase (PG), etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid and relatively low-cost of generation of genomic sequences and other 'omics' datasets has played a significant role in furthering our understanding of the host-pathogen interactions and ecology of Rhizoctonia species. (8)(9)(10)(11)(12). The analysis of these genomic sequences and functional components revealed several novel or previously unrecognized classes of R. solani genes among different AGs that are .…”
Section: Introductionmentioning
confidence: 99%
“…However, the population dynamics and pathogenicity of R. solani, as affected by organic substrates, has received limited attention [29]. R. solani is a basidiomycetal fungus with the ability to produce a broad array of plant cell-walldegrading enzymes [30,31]. These are used for decomposition of cellulose, as part of both necrotrophic and saprotrophic growth of R. solani [25,32].…”
Section: Introductionmentioning
confidence: 99%